The Influence of Management Information System (MIS) on the Effectiveness of Finance Department Performance - Puranto, Andre Puji (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine how influential the use of Management Information Systems (MIS) is in improving performance effectiveness, facilitating data processing and collection, ensuring data accuracy, and facilitating the data delivery process. This study was conducted using a qualitative method using articles related to the influence of the implementation of Management Information Systems (MIS) from previous studies to strengthen arguments related to the influence of the implementation of Management Information Systems (MIS) in a company. The results of this study are expected to provide insight to readers regarding how much influence the use of Management Information Systems (MIS) has in improving work effectiveness, facilitating data processing and collection, ensuring data accuracy, and facilitating the data delivery process, especially in financial management.